Globalization, Poverty, and Inequality since 1980 - Dollar, David (Oxford University Press on behalf of the World Bank, 2013)
One of the most contentious issues of globalization is the effect of global economic integration on inequality and poverty. This article documents five trends in the modern era of globalization, starting around 1980. The first trend is that growth rates in poor economies have accelerated and are higher than growth rates in rich countries for the first time in modern history. Developing countries per capita incomes grew more than 3.5 percent a year in the 1990s. Second, the number of extremely poor people in the world has declined significantly. The share of people in developing economies living on less than dollar 1 a day has been cut in half since 1981, though the decline in the share living on less than dollar 2 per day was much less dramatic. Third, global inequality has declined modestly, reversing a 200-year trend toward higher inequality. Fourth, within-country inequality in general is not growing, though it has risen in several populous countries (China, India, and the United States). Fifth, wage inequality is rising worldwide. This may seem to contradict the fourth trend, but it does not because there is no simple link between wage inequality and household income inequality. Furthermore, the trends toward faster growth and poverty reduction are strongest in developing economies that have integrated with the global economy most rapidly, which supports the view that integration has been a positive force for improving the lives of people in developing areas